Economic analysis of using e-glass composite wrap repair system for pipelines in Malaysia - Mohamed Ariff, Tasnim Firdaus; Azmi , Mohamad Asyraf; Bahar, Rubina (AENSI, 2014)
One of the biggest problems faced by the oil and gas industries is transmitting gas when there is a damaged pipeline. This damage may be a result from corrosion, crack or a burst pipe. Damaged pipelines need a safe, quick and efficient repair mechanism to prevent any further extensive damage. There are various methods and repair systems that offer different advantages and limitations to the oil and gas industries. Composite wrap repair system is a new technology that is being used in the United States of America and some European countries. However, this technology has not penetrated into the South East Asian region yet. This study is done with the aim of determining the feasibility of implementing this repair system into the Malaysian oil and gas industries. E-Glass fiber was selected since it is the most suitable and appropriate type of composite that can be adapted for the composite wrap. Then, cost analysis was done for this composite repair system and compared with the welding repair and pipeline replacement methods. Calculations for the result of every repair system were performed to compare the most efficient method. E-Glass fiber composite wrap has shown to be the most economical technique when compared with the welding and pipe replacement methods.